theorem excons (a: nat) {x y: nat}: $ a != 0 <-> E. x E. y a = x : y $;
Step | Hyp | Ref | Expression |
1 |
|
consfstsnd |
a != 0 -> fst (a - 1) : snd (a - 1) = a |
2 |
|
anll |
fst (a - 1) : snd (a - 1) = a /\ x = fst (a - 1) /\ y = snd (a - 1) -> fst (a - 1) : snd (a - 1) = a |
3 |
|
anlr |
fst (a - 1) : snd (a - 1) = a /\ x = fst (a - 1) /\ y = snd (a - 1) -> x = fst (a - 1) |
4 |
|
anr |
fst (a - 1) : snd (a - 1) = a /\ x = fst (a - 1) /\ y = snd (a - 1) -> y = snd (a - 1) |
5 |
3, 4 |
conseqd |
fst (a - 1) : snd (a - 1) = a /\ x = fst (a - 1) /\ y = snd (a - 1) -> x : y = fst (a - 1) : snd (a - 1) |
6 |
5 |
eqcomd |
fst (a - 1) : snd (a - 1) = a /\ x = fst (a - 1) /\ y = snd (a - 1) -> fst (a - 1) : snd (a - 1) = x : y |
7 |
2, 6 |
eqtr3d |
fst (a - 1) : snd (a - 1) = a /\ x = fst (a - 1) /\ y = snd (a - 1) -> a = x : y |
8 |
7 |
iexde |
fst (a - 1) : snd (a - 1) = a /\ x = fst (a - 1) -> E. y a = x : y |
9 |
8 |
iexde |
fst (a - 1) : snd (a - 1) = a -> E. x E. y a = x : y |
10 |
1, 9 |
rsyl |
a != 0 -> E. x E. y a = x : y |
11 |
|
consne0 |
x : y != 0 |
12 |
|
neeq1 |
a = x : y -> (a != 0 <-> x : y != 0) |
13 |
11, 12 |
mpbiri |
a = x : y -> a != 0 |
14 |
13 |
eex |
E. y a = x : y -> a != 0 |
15 |
14 |
eex |
E. x E. y a = x : y -> a != 0 |
16 |
10, 15 |
ibii |
a != 0 <-> E. x E. y a = x : y |
Axiom use
axs_prop_calc
(ax_1,
ax_2,
ax_3,
ax_mp,
itru),
axs_pred_calc
(ax_gen,
ax_4,
ax_5,
ax_6,
ax_7,
ax_10,
ax_11,
ax_12),
axs_set
(elab,
ax_8),
axs_the
(theid,
the0),
axs_peano
(peano1,
peano2,
peano5,
addeq,
muleq,
add0,
addS,
mul0,
mulS)